LINGUISTICS, LITERATURE, TOURISM: STUDENTS’ TOPIC IN WRITING GRADUATING PAPER AT ENGLISH DEPARTMENT FIB UNSAP SUMEDANG - Imas Maryanah (ReALL - Research on Applied Linguistics and Literature, 2022)
Academic writing is really essential to master by students. For this reason, those who want to finish studying at any level of degree must write graduating paper. It becomes one of the requirements to get Sarjana, Master, and Doctoral degree. Every program has determined several kinds of topics that the students should select. Basically, this study aims at 1) describing students’ topic in writing their graduating paper to get Sarjana degree since 2005-2018; and 2) exploring their reasons for selecting those topics. There are three main theories applied in this study, namely, the theory of linguistics, literature, and tourism. To strengthen the main theories Hadaway, Vardell, and Young’s statement (2002) is also taken. It is also added by some supporting theories from Grant (1988), Finegan, Blair, and Collin (2000), and others. Then, the qualitative research design is an appropriate method used in this study. The research site is at Fakultas Ilmu Budaya (FIB) UNSAP Sumedang. While the object of the research was the students and their graduating papers from the academic year 2005/2006 to 2018/2019. Hence, to collect data, it was applied observation, interviews and library research in order to find out complete documents. Relevant to this, descriptive research was conducted to analyze data by applying some steps. The result shows that most students had chosen topics covering linguistics, literature, and tourism. They selected such kinds of topics based on their interest and hobby as their curiosity to know the concept and its meaning, to apply theories, and to understand the description of things. Then, it is the focus of the topic on certain materials because of their comprehension of the subject. The last is popular themes as choices among others. It can be concluded that students have a variety of thinking in selecting topics for graduating papers. This happened because they were motivated by enjoyment to do the writing process, the curiosity of proving something (theories, social life situations), and comprehension of a certain subject.